2007
DOI: 10.5465/amj.2007.26279210
|View full text |Cite
|
Sign up to set email alerts
|

Ownership form, Managerial Incentives, and the Intensity Of Rivalry

Abstract: JAVIER GIMENO INSEADThis study investigates how differences in ownership form-between franchised and company-owned units-affect managerial incentives and competitive pricing in different oligopolistic contexts. We argue that chains may restrict decision making in company-owned units as a commitment device to maintain high prices in concentrated markets and found evidence consistent with this argument. We also found that a unit's ownership form affected its rivals' competitive behavior. Our results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 50 publications
4
71
0
2
Order By: Relevance
“…Authors regard it mainly as complementary to more complex indexes (Wu, 2012;Jankowska and Bartosik-Purgat, 2012), which is also confirmed by the procedure used in the literature review, without indicating a single publication in which it would constitute a single method of measuring the intensity of competition. The number of competitors is most commonly used in conjunction with the Herfindahl--Hirschman Index (Li et al, 2008;Vroom and Gimeno, 2007), as well as multi-dimen sional indexes of competition intensity (Ye et al 2008), or even as one of the points in the questionnaire (Tsaur and Wang, 2011). …”
Section: Quantitative Measures Based On the Number Of Companies And Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors regard it mainly as complementary to more complex indexes (Wu, 2012;Jankowska and Bartosik-Purgat, 2012), which is also confirmed by the procedure used in the literature review, without indicating a single publication in which it would constitute a single method of measuring the intensity of competition. The number of competitors is most commonly used in conjunction with the Herfindahl--Hirschman Index (Li et al, 2008;Vroom and Gimeno, 2007), as well as multi-dimen sional indexes of competition intensity (Ye et al 2008), or even as one of the points in the questionnaire (Tsaur and Wang, 2011). …”
Section: Quantitative Measures Based On the Number Of Companies And Tmentioning
confidence: 99%
“…The Herfindahl index takes into account the market shares of individual actors or, more accurately, the sum of the squares of these shares (Jermias, 2006;Vroom and Gimeno, 2007;Bajtelsmit and Bouzouita 1998). HHI was referred to in eight publica tions selected as part of a systematic literature review -in seven as the basic measure of competition intensity.…”
Section: Measures Of Competitive Intensity -Analysis Based On Literatmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the contingency theory, Yin and Zajac (2004) studied how flexible and decentralized structures moderate the relationship between franchising and performance. Vroom and Gimeno (2007) examined the local competition as a moderator in franchised outlets, and found that both franchised and company-owned outlets benefit from having few competitors, but company-owned outlets benefit more.…”
Section: Contingency Theorymentioning
confidence: 99%
“…The competitive pressure of the marketplace affects firm performance as well (Mesquita et al, 2008). Vroom and Gimeno (2007) examined the local competition as a moderator in franchised outlets and found both franchised and company-owned outlets benefit from having fewer competitors.…”
Section: Environmental Factors In Absorptive Capacitymentioning
confidence: 99%